A novel lapping process for single-crystal sapphire using hybrid nanoparticle suspensions. (1st February 2021) - Huang, Shuiquan; Li, Xuliang; Zhao, Yitian; Sun, Qiang; Huang, Han
Highlights: This manuscript presents a novel lapping process for shaping single-crystal sapphire, whose performance is chemically enhanced by using Al2 O3 /GO nanoparticle suspensions. The performance of the hybrid nanosuspensions in the lapping of sapphire is superior to the conventionally used diamond suspensions. The multidisciplinary science involved in the deformation and removal of the new lapping process was comprehensively understood using advanced materials characterisation tools. It offers a practical and efficient approach for future nanoscale machining of hard and brittle materials. Abstract: Single-crystal sapphire is an important material with increasingly more widespread applications in optics, semiconductor and laser-related devices. However, its high hardness and brittleness have posed significant challenges for the efficient machining of sapphire with a satisfactory surface integrity. In this work, a new lapping process was developed for sapphire using a novel suspension that was made by dimensionally integrating alumina (Al2 O3 ) nanoparticles with graphene oxide (GO) nanosheets in pure water. The performance of the Al2 O3 /GO hybrid nanosuspensions in the lapping of sapphire was systematically investigated using commercial diamond suspensions as the benchmarks. The multidisciplinary science involved in the new lapping process was unveiled. The use of the hybrid nanosuspensions during lapping enabled the generation of an oxide layer on the sapphire surface that was softer than its pristine substrate. This process thus simultaneously improved the removal efficiency and enhanced the surface quality, in comparison to conventional lapping. Graphical abstract: Image, graphical abstract